The Blessing of Waters and Epiphany: The Eastern Liturgical Tradition. By Nicholas Denysenko - Wybrew, Hugh (The journal of theological studies, 2013)
In the Eastern Christian tradition Epiphany celebrates the baptism of Jesus and the attendant revelation of God as Trinity: at the Jordan the Father’s voice proclaims Jesus as the divine Son, and the Holy Spirit comes upon him. The entry of the Second Person of the Trinity into the waters of the Jordan sanctifies all water; and in Orthodox churches the blessing of water is a prominent aspect of the feast’s liturgical celebrations. Blessed water is taken home to be kept and used by the faithful during the ensuing year, and is drunk for the forgiveness of sins and healing of soul and body.